Perlindungan Hukum Terhadap Perempuan Sebagai Korban Kekerasan Dalam Rumah Tangga - Elfina Cahyaningtyas; Indra Yudha Koswara (Peneliti.net, 2023)
The purpose of this research is to find out the legal protection for women victims of domestic violence. This study uses normative legal research methods, this study uses secondary legal materials by examining literature related to Law Number 23 of 2004 concerning the Elimination of Domestic Violence. It can be concluded, according to article 10a of the Law on the Elimination of Domestic Violence, victims are entitled to receive protection from several parties, such as advocates, social institutions, prosecutors, police, courts, family or other parties, either temporarily or based on the government's stipulation of protection from the court. Meanwhile, the impacts experienced by women victims of domestic violence are experiencing physical injuries or injuries, mental disorders, loss of self-confidence and self-esteem, feelings of helplessness, dependence on husbands who torture them, stress, trauma, depression as a result of violence.